1995
DOI: 10.1002/jbmr.5650100308
|View full text |Cite
|
Sign up to set email alerts
|

Bone density in young women is associated with body weight and muscle strength but not dietary intakes

Abstract: Potential determinants of bone mineral density (BMD) were studied cross-sectionally in 115 healthy, sexually mature Caucasian women aged 18 years. Bone mineral density (Hologic QDR1000W) of the lumbar spine, proximal femur (five sites), and distal tibia and fibula; fasting blood and urine calcium biochemistry; serum sex hormone levels (follicular phase); nutrient intakes; aerobic fitness; trunk muscle strength; and habitual activity levels were measured. The effects of heredity were considered by measuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(34 citation statements)
references
References 50 publications
4
25
0
1
Order By: Relevance
“…This finding is consistent with previous literature in which weight was a primary predictor of WB, LS, and PF BMD [36][37][38]. Of soft tissue components, lean mass has been shown to be the strongest predictor of BMD in young women without MS [23,[39][40][41][42][43] and in adults and older women without MS [36,[44][45][46][47], whereas other studies have shown that fat mass is associated with bone health [21,23,48]. Differences between these findings may be the result of age, since this may affect soft tissue predictors of BMD, with lean mass being a stronger predictor in young women without MS and fat mass having a stronger association with BMD in postmenopausal women without MS [21][22][23].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with previous literature in which weight was a primary predictor of WB, LS, and PF BMD [36][37][38]. Of soft tissue components, lean mass has been shown to be the strongest predictor of BMD in young women without MS [23,[39][40][41][42][43] and in adults and older women without MS [36,[44][45][46][47], whereas other studies have shown that fat mass is associated with bone health [21,23,48]. Differences between these findings may be the result of age, since this may affect soft tissue predictors of BMD, with lean mass being a stronger predictor in young women without MS and fat mass having a stronger association with BMD in postmenopausal women without MS [21][22][23].…”
Section: Discussionsupporting
confidence: 91%
“…However, the mean weight and BMI values of the two groups of patients did not differ significantly. Other studies have also shown an association between body weight (14,15) and BMI (1,11,22,(30)(31)(32)(33) with BMD. But, Saravi et al (4) reported no significant effect of BMI on BMD.…”
Section: Discussionmentioning
confidence: 88%
“…This disease is characterized by low bone mass and destruction of bone tissue, leading to increased fracture risk (1,2,6). Several studied have shown that in addition to the risk factors such as aging, lack of physical activity, smoking, premature menopause, family history, poor diet and low intake of calcium and vitamin D (3,5,(7)(8)(9)(10)(11)(12), other factors, including body weight (13)(14)(15) and BMI (1,3,5,9,(11)(12)(13)16) are also important in the risk assessment tools, which contribute to osteoporosis and osteoporotic fracture risk. Measurement of body mass index is an inexpensive and valuable technique to guide public health policy, clinical decisions, and evaluation of nutritional status (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound-derived prediction equations are capable of taking measurements in the field, and are safe and valid in predicting total and regional SM mass (Sanada et al, 2006). Some investigators have shown that prolonged low-tomoderate intensity exercise is independently associated with higher BMD (Nguyen et al, 1998;Hagberg et al, 2001;Pongchaiyakul et al, 2004), while cardiorespiratory fitness (VO 2 peak) is only slightly correlated with bone mineral indices (Henderson et al, 1995;Ryan and Elahi, 1998;Lynch et al, 2002). In this study, VO 2 peak (normalized to body mass) in young women was significantly correlated with BMD (Po0.05), while VO 2 peak (normalized to whole-body SM mass) was not significantly associated with BMD (Table 5).…”
Section: Discussionmentioning
confidence: 99%